Lenvatinib and pembrolizumab in patients with advanced uterine cancer - A. G. Kedrova; A. I. Berishvili; Т. А. Greyan (ABV-press, 2021)
Uterine cancer is one of the few cancers with an increasing incidence and mortality rate in developed countries, which partly reflects the increasing prevalence of obesity and aging of the female population. Despite the fact that uterine cancer is usually diagnosed when lesions have affected only the uterine body, searching for new treatment regimens for advanced disease remains highly relevant due to unsatisfactory results of chemotherapy and high mortality among women with stage III-IV uterine cancer. In this article, we discuss the main aspects of using lenvatinib and pembrolizumab that have been approved by the US Food and Drug Administration (FDA), Australian Therapeutic Goods Administration (TGA), and Ministry of Health of Canada (HC). The lenvatinib + pembrolizumab scheme showed its efficacy (38.3 % objective responses) and safety (grade III and IV adverse events were reported in 83 (66.9%) of 124 patients) in 94 patients with advanced endometrial cancer whose tumors did not show signs of microsatellite instability (MSI) and defective DNA mismatch repair system. In 25 (69 %) patients who responded to treatment, the time to response was more than 6 months. In this article, we also report a case of progressive uterine cancer in a patient, who benefited from therapy with the combination of lenvatinib and pembrolizumab. We also describe adverse events of such therapy and ways of their management.